2012
DOI: 10.1111/j.1937-5956.2011.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Logistics Performance on Trade

Abstract: This paper studies the impact of logistics performance on global bilateral trade. Taking a supply chain perspective, logistics performance refers to cost, time, and complexity in accomplishing import and export activities. We draw on a data set compiled by the World Bank containing specific quantitative metrics of logistics performance in terms of time, cost, and variability in time. Numerous researchers have shown that logistics performance is statistically significantly related to the volume of bilateral tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(104 citation statements)
references
References 32 publications
8
93
0
3
Order By: Relevance
“…However, quality of port infrastructure significantly affects the logistics performance of a country. Similar to Hausman et al (2013), we also found that logistics performance affects the seaborne trade of a country. Most of the studies that foresaw diminishing impact of seaports on economy emphasised employment generation within ports (Gripaios and Gripaios, 1995;Kinsey, 1981;Jung, 2011).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, quality of port infrastructure significantly affects the logistics performance of a country. Similar to Hausman et al (2013), we also found that logistics performance affects the seaborne trade of a country. Most of the studies that foresaw diminishing impact of seaports on economy emphasised employment generation within ports (Gripaios and Gripaios, 1995;Kinsey, 1981;Jung, 2011).…”
Section: Discussionsupporting
confidence: 77%
“…Also, better accessibility of freight increases logistics employment (van den Heuvel et al, 2014). Overall, firms in countries with better logistics performance have higher probability of exporting to international markets and attracting foreign direct investments (Hausman et al, 2013). Thus, logistics development has a positive impact on regional economic growth (Chu, 2012;Lean et al, 2014;Li et al, 2017;Lun et al, 2016).…”
Section: H1 (F )mentioning
confidence: 99%
“…Each additional day that a product is delayed prior to being shipped reduces trade by at least 1 per cent, as found by Djankov et al (2010). A result which combines the effects of time and costs is obtained by Hausman et al (2013). In their study, a 1% reduction in processing costs/time leads to 0.49%-0.37% of increased bilateral trade.…”
Section: Literaturementioning
confidence: 87%
“…Hausman et al (2013) estimate that a 1% reduction in the 'distance' measure, which can be interpreted as shipping costs, increases trade by 1.4%. Similarly, a 1% reduction in the total trade-related processing cost would be associated with a 0.5% increase in bilateral trade (Hausman, et al, 2013).…”
Section: Ease Of Arranging Competitively Priced Shipmentsmentioning
confidence: 99%